PENGARUH DANA PIHAK KETIGA, CAPITAL ADEQUANCY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP KINERJA KEUANGAN PADA SEKTOR PERBANKAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Rosdiana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this research is to examine influence of third-party funds, capital adequacy ratio, loan to deposit ratio throught financial performance of public banking listed at Indonesian Stock Exchange during 2018-2021. Population of this research are Commercial Bank that registered in Indonesian Stock Exchange from 2018 till 2021. Data on this research are coming from in Indonesia Stock Exchange. Sample are choosen by purposive sampling method at least 25 company. Data’s test technique by using multiple linear regression analyze. The result showed that the third-party funds, capital adequacy ratio has a positive effect on return on asset and loan to deposit ratio has a negative effect on return on asset.